2005
DOI: 10.1007/s10528-005-5211-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism for Transforming Growth Factor Beta 1-509 (TGF-B1-509): Association with Endometriosis

Abstract: Transforming growth factor beta (TGF-B) family members are multi-functional cytokines that play a key role in cellular growth, proliferation, and differentiation. The aim of the study was to investigate whether the TGF-B1-509 gene polymorphism could be used as a marker of susceptibility in endometriosis. Women were divided into two groups: endometriosis (n = 150) and non-endometriosis (n = 159). Polymorphisms for TGF-B 1-509 genes were amplified by polymerase chain reaction and detected after restriction enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 30 publications
0
28
1
4
Order By: Relevance
“…To the best of our knowledge, this is the second report to investigate an association between the À509 C/T polymorphism and endometriosis. The first study reported that the TT genotype and T allele were associated with a higher susceptibility to endometriosis in a Chinese population (19). In that study, there were no control women with T homozygote, but the proportion of endometriosis patients with T homozygote was 29.4%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To the best of our knowledge, this is the second report to investigate an association between the À509 C/T polymorphism and endometriosis. The first study reported that the TT genotype and T allele were associated with a higher susceptibility to endometriosis in a Chinese population (19). In that study, there were no control women with T homozygote, but the proportion of endometriosis patients with T homozygote was 29.4%.…”
Section: Discussionmentioning
confidence: 96%
“…However, only one study has explored the association between the TGF-b gene polymorphism and the risk of endometriosis. Hsieh et al (19) reported that the À509 C/T polymorphism in the TGF-b1 gene was associated with an increased risk for endometriosis in a Chinese population.…”
mentioning
confidence: 99%
“…The burden of breast cancer is increasing in both developed and developing countries. TGFB1 is a member of the transforming growth factor beta (TGFB) family and works as a multi-functional cytokine that plays a key role in cellular growth, proliferation, and differentiation [1]. TGFB has three isoforms TGFB1, TGFB2, and TGFB3, while TGFB1 is the most abundant and universally expressed isoform [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several lines of genetic-association studies have revealed associations between the development of endometriosis and certain genetic polymorphisms. However, the genes that play a role in susceptibility to the development and progression of endometriosis are still unknown (Hsieh et al, 2005;Luisi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%